The Urgency of Design on Indigenous Community Law Based on the Conflict of Torakat Indigenous People in North Sulawesi - Suandi Suandi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This study aims to find out and analyze the urgency of the Indigenous Peoples Bill in terms of the Toruakat Indigenous People's conflict in North Sulawesi. The method used in this study is a normative juridical method, with secondary data sources as the primary data, and then the collected data is analyzed qualitatively. After conducting research, it was found that the conflict occurred between the Indigenous Peoples of Touakat and PT. Bulawan Daya Lestari, in Bolaang Mongondow, North Sulawesi, resulted in the death of one indigenous person and the injury of four other indigenous people, arguably revealing that the Government cannot be present to protect indigenous peoples. The protection, fulfilment, and recognition of indigenous peoples should be related to the substance of human rights contained in the 1945 Constitution of the Republic of Indonesia. This means that the existence of confirmation in the Constitution is not only limited to recognizing the constitutional rights of indigenous peoples but also must guarantee the fulfilment of the rights of indigenous peoples. -the constitutional rights. The occurrence of the conflict can ultimately show that there is an urgency for the Indigenous Peoples Bill